Analisa Proses Pengecoran Material Aluminium Secara Sentripugal Terhadap Kecepatan Putar - Rasyidi Rasyidi (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
One of the methods in casting process is centrifugal casting. Generally, it is used to make a product in the form of cylinder or symmetric on spin mold. Thus, it is necessary to discuss further about the influence of rotation velocity variation on the quality of Aluminum casting product that enwrap mechanical characteristic and micro structure. The velocity variations that chosen are 175 rpm, 200 rpm and 235 rpm. This experiment is executed by looking at micro structure that is produced on each rotation variation especially the part of cross section of casting product. Then, it can be done a discussion about micro structure relation towards the hardness number on each rotation variation. In the observation of micro structure, grain structure that is produced by centrifugal casting is generally equiaxed and columnar with the orientation of direction in accordance with the direction of machine velocity. From the result of Vickers hardness test, it can be seen that rotation variation on 235 rpm show higher hardness number rather than another rotation variation.